Predictive value of EEG-derived pain threshold index for acute postoperative pain in children - Lv, Jingjing; Zhang, Jianwei; Zhang, Kan; Zheng, Jijian (Frontiers in Pediatrics, 2022)
Background Electroencephalogram (EEG)-derived pain threshold index (PTI) has been developed as a novel pain recognition indicator and has been proved to be useful in the prediction of acute postoperative pain in adults. Evidence of its usability in children is limited. The aim of this study was to investigate the prediction value of this novel pain indicator PTI for acute postoperative pain in children. Methods A total of 80 patients undergoing laparoscopic surgery under general anesthesia were enrolled. Blood pressure, heart rate (HR), surgical pleth index (SPI), PTI, and EEG-derived sedative index-wavelet index (WLI) data were recorded at the end of the surgery. The postoperative pain scores Face, Legs, Activity, Cry, Consolability (FLACC) were obtained in the emergence room 5 min after the children wake up. Receiver-operating characteristic curve was performed to analyze the predictive value of PTI, SPI, HR, and mean arterial pressure (MAP). The consistency between SPI and PTI was also evaluated. Results Results showed that the areas under curves (95%CI) of PTI and SPI were 0.796 (95% CI: 0.694–0.895) and 0.753 (95% CI: 0.632–0.874), respectively, with the best cut-off value of 58 and 45 to discriminate between mild and moderate to severe pain. Conclusion This study suggested that PTI obtained at the end of the surgery could predict acute postoperative pain in children with an acceptable accuracy. It will help with early recognition and treatment of postoperative pain, thus reducing the pain in children. In addition, PTI had a good consistency with SPI in predicting acute postoperative pain in children.